2021
DOI: 10.1186/s12913-021-07168-8
|View full text |Cite
|
Sign up to set email alerts
|

Confronting complexity and supporting transformation through health systems mapping: a case study

Abstract: Introduction Health systems are a complex web of interacting and interconnected parts; introducing an intervention, or the allocation of resources, in one sector can have effects across other sectors and impact the entire system. A prerequisite for effective health system reorganisation or transformation is a broad and common understanding of the current system amongst stakeholders and innovators. Chronic obstructive pulmonary disease (COPD) and heart failure (HF) are common chronic diseases wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Second, this study indicates that distance monitoring service, on the operational level, creates several opportunities for better management of healthcare demand since the changes in the care delivery process fit with four demand-capacity management strategies found in the literature, namely increasing patients’ participation, segmenting and rechanneling the patients, and flexible and multiskilled nurses. This finding is in line with the findings of studies focusing on preventive and self-management care for patients with chronic ailments [ 5 , 75 ]. However, on the strategic level, these strategies have yet to be devised and implemented.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Second, this study indicates that distance monitoring service, on the operational level, creates several opportunities for better management of healthcare demand since the changes in the care delivery process fit with four demand-capacity management strategies found in the literature, namely increasing patients’ participation, segmenting and rechanneling the patients, and flexible and multiskilled nurses. This finding is in line with the findings of studies focusing on preventive and self-management care for patients with chronic ailments [ 5 , 75 ]. However, on the strategic level, these strategies have yet to be devised and implemented.…”
Section: Discussionsupporting
confidence: 90%
“…The global burden of chronic disease is enormous, and it is currently one of the top ten causes of death worldwide [ 3 ]. Illnesses such as chronic obstructive pulmonary disease (COPD) and heart failure (HF) increase hospital admissions and the number of visits to general physicians, exerting additional pressure on healthcare resources and reducing the quality of care [ 4 , 5 ]. These chronic diseases are also recognized as among the main causes of comorbidity [ 6 ] that increase the demand for healthcare even more.…”
Section: Introductionmentioning
confidence: 99%
“…After these discussions, the primary investigators will create a systems map ( Figure 2 ) including the variables identified through the stakeholder feedback. The systems map can help evaluate the relationships between variables and guide the researchers where to focus [ 83 , 84 , 85 , 86 ]. Using the systems map in Figure 2 , the researcher might decide to focus on horse movement patterns, as multiple connections from all sectors lead to this variable.…”
Section: The One Health Modelmentioning
confidence: 99%
“…A critical element of this selection process was consensus and evidence that local assets (notably the Best Care Team) could be leveraged within this sub-population to generate improvement in experiences, outcomes, and total cost of care across the system. 19 , 20 WOHT leveraged ongoing and established work to support this population as a way to make an even greater impact on the equity-driven Quadruple Aim, specifically health outcomes and patient and provider experiences. It was also felt that this sub-population offered a foundation for change that could demonstrate the principles of integrated care and population health management extending beyond traditional medical care.…”
Section: Early Days (Committing To a Vision)mentioning
confidence: 99%